Trading translation with RNA-binding proteins - Abaza, Irina (Cold Spring Harbor Laboratory Press, 2008)
RNA-binding proteins regulate every aspect of RNA metabolism, including pre-mRNA splicing, mRNA trafficking, stability, and translation. This review summarizes the available information on molecular mechanisms of translational repression by RNA-binding proteins. By using a specific set of well-defined examples, we also describe how regulation can be reversed.